2021
DOI: 10.3390/ijms22105221
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the APETALA2 (AP2) Transcription Factor in Dendrobium officinale

Abstract: The APETALA2 (AP2) transcription factors (TFs) play crucial roles in regulating development in plants. However, a comprehensive analysis of the AP2 family members in a valuable Chinese herbal orchid, Dendrobium officinale, or in other orchids, is limited. In this study, the 14 DoAP2 TFs that were identified from the D. officinale genome and named DoAP2-1 to DoAP2-14 were divided into three clades: euAP2, euANT, and basalANT. The promoters of all DoAP2 genes contained cis-regulatory elements related to plant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…For instance, in ‘ABC’ model of flower development, APETALA2 ( AP2 ) as an A-class gene took part in flower formation [ 17 ]. Recently, researchers have found that the expressions of two DoAP2 genes ( DoAP2–8 and DoAP2–10 ) were down-regulated and another two AP2 genes ( DoAP2–2 and DoAP2–3 ) were up-related during flower development, which suggested that DoAP2 genes contribute to plant regeneration and flower development in Dendrobium officinale [ 18 ]. Overexpression of miR172, whose target is AP2 -like gene, resulted in the double flower phenotype in roses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in ‘ABC’ model of flower development, APETALA2 ( AP2 ) as an A-class gene took part in flower formation [ 17 ]. Recently, researchers have found that the expressions of two DoAP2 genes ( DoAP2–8 and DoAP2–10 ) were down-regulated and another two AP2 genes ( DoAP2–2 and DoAP2–3 ) were up-related during flower development, which suggested that DoAP2 genes contribute to plant regeneration and flower development in Dendrobium officinale [ 18 ]. Overexpression of miR172, whose target is AP2 -like gene, resulted in the double flower phenotype in roses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…BBM, encoding an AP2 domain protein, is a key regulator of somatic embryo development in monocot plants like rice and in dicot plants like Arabidopsis (Boutilier et al, 2002; Khanday et al, 2020). In our previous study, two genes (DoAP2-4 and DoAP2-13) annotated as BBM genes, did not preferentially express in PLBs in Dendrobium orchid (Zeng et al, 2021). The marker of somatic embryo development gene SERK is abundant in the zygotic embryos of sunflowers (Thomas et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…The coding sequences of DoSTM and DoERF5 were cloned into the pSAT6–EYFP–N1 expression vector and fused in‐frame with YFP. The recombinant construct and plasmid of the nuclear localization marker (NLS–mCherry) were co‐transformed into Arabidopsis mesophyll protoplasts as previously described (Zeng et al, 2021). The primers used for subcellular localization analysis are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Apetala 2 ( AP2 ) is a gene that codes for a transcription factor, and it belongs the AP2 / EREBP gene family, which plays key roles in regulating growth and development in plants. Zeng et al identified 14 homologs of AP2 in a popular medicinal orchid, Dendrobium officinale Kimura & Migo, namely DoAP2-1 to DoAP2-14 [ 5 ]. After subcellular localization and functional analysis of these genes, it was found that DoAP2 may encode transcriptional repressors and be involved in flower development, stress response and other biological activities.…”
Section: Pollination and Flowering Biologymentioning
confidence: 99%